The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.heares.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic trauma triggers upregulation of serotonin receptor genes

Abstract: Hearing loss induces plasticity in excitatory and inhibitory neurotransmitter systems in auditory brain regions. Excitatory-inhibitory balance is also influenced by a range of neuromodulatory regulatory systems, but less is known about the effects of auditory damage on these networks. In this work, we studied the effects of acoustic trauma on neuromodulatory plasticity in the auditory midbrain of CBA/J mice. Quantitative PCR was used to measure the expression of serotonergic and GABAergic receptor genes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…[ 23 ] Acoustic trauma in an animal model induced substantial hearing loss and caused selective upregulation of serotonin receptor genes in the inferior colliculus. [ 24 ] These 3 studies have demonstrated that hearing loss may induce plasticity in the excitatory and inhibitory neurotransmitter systems in the central auditory brain regions. However, information on networks and etiologic mechanisms between auditory damage and depression via the serotonin pathway is scant.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Acoustic trauma in an animal model induced substantial hearing loss and caused selective upregulation of serotonin receptor genes in the inferior colliculus. [ 24 ] These 3 studies have demonstrated that hearing loss may induce plasticity in the excitatory and inhibitory neurotransmitter systems in the central auditory brain regions. However, information on networks and etiologic mechanisms between auditory damage and depression via the serotonin pathway is scant.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression relative to the housekeeping gene (Rpl13a) was calculated with the method used by [ 93 ], in which corrections for different efficiencies between target gene and housekeeping gene are made: in which RE is the relative expression, Ekhg is the efficiency of the housekeeping gene, CThkg is the Ct value of the housekeeping gene, Etg is the efficiency of the target gene, and CTtg is the Ct value of the target gene.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, activating serotonergic pathways in the IC strongly influences responses of IC neurons to playbacks of squeaks. Activating the 5-HT1A receptor, a type which is strongly expressed within the IC (Thompson et al 1994;Peruzzi and Dut 2004;Smith et al 2014), greatly decreases the responses of IC neurons to squeaks (Hurley and Nigam 2014). 5-HT1A activation also consolidates squeak-evoked action potentials in time, so that information on the temporally varying acoustic structure of squeaks is also reduced.…”
Section: Model Of Contextual Feedback To the Auditory Midbrainmentioning
confidence: 99%